Kepuasan Nasabah Ditinjau dari Pelayanan, Relationship Marketing dan Loyalitas di KSPPS Dana Amanah Karanganyar - Lina, Lina (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The aims of this study are (1) to determine the effect of service on customer satisfaction. (2) To determine the effect of relationship marketing on customer satisfaction. (3) To determine the effect of loyalty on customer satisfaction. The research design iis descriptive quantitative. This research was conducted on KSPPS Dana Amanah customers in Karanganyar. The population iin this study iis 1,000. The sample iin this research is 100 respondents. The sampling technique used iis purposive sampling method. Collect data through questionnaires. Multiple linear regression test, F test, t test, and the coefficient of determination are data analysis techniques that use statistical analysis. The results showed that partially, service had a significant positive effect on KSPPS Dana Amanah customer satisfaction. Partially, relationship marketing has a significant positive effect on KSPPS Dana Amanah customer satisfaction. Partially, loyalty has a significant positive effect on KSPPS Dana Amanah customer satisfaction. Simultaneously, service, relationship marketing, loyalty have a significant positive effect on KSPPS Dana Amanah customer satisfaction.